HUBUNGAN DAYA TAHAN OTOT LENGAN DAN BAHU DAN POWER OTOT TUNGKAI DENGAN HASIL 50 METER RENANG GAYA DADA PADA ATLET PPLP PROVINSI RIAU - Intan Sri Herdianti; Zainur Zainur; Ni Putu Nita Wijayati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : Based on observation on an athlete pplp riau, that athletebis still not to optimize the use of swimming pool the breaststroke, this was apparent from public work while conducting a swimming pool the breaststroke there are still many an athlete they did not fulfill the desired time occurred as a result of exhaustion the arm muscles and power limb muscles of. Percent of the population is that the whole a subject of study”. An objective in this research is to look at the relationship of the arm and shoulder muscle endurance and power limb muscles with the results of 50 meters swimming the breaststroke on an athlete pplp riau .It is a whole population in research swimming athletes son of pplp riau which consisted of six of the .Because the size of the population less than 100 that is in pplp riau , so sampling technique used is a technique or the withdrawal sample population sample saturated ( total sampling ) so that a total of six of the sample . The research is instrument push-up test, standing broad jump swimming the breaststroke and the 50 meters. Based on the research that has been in the previous writer disassemble, it can be taken the conclusion is results, then; There was no correlation that means between endurance the arm muscles and shoulders with the results of 50 meters swimming the breaststroke in pplp riau of rhitung 0,457 < rtabel 0,878. There was no correlation that means between power limb muscles with the results of 50 meters swimming the breaststroke in pplp riau of rhitung 0,585 < rtabel 0,878. There was no correlation that means between endurance the arm muscles and shoulders and power limb muscles with the results of 50 meters swimming the breaststroke in pplp riau of rhitung 0,646 < rtabel 0,878.Key words: durability on a muscle of the arm and shoulder, power limb muscles of the results of 50 meters swimming pool the breaststroke